Macroscopic crack ratio as a structural surrogate linking linear filtration and nonlinear expression in sludge dewatering - Yi-Wen Yuan; Hao-Ran Chen; Zhi-Hao Liu; Shi-Yu Ren; Chang-Ji Huang; Raymond Jianxiong Zeng; Hou-Feng Wang (Process Safety and Environmental Protection, 2026)

Soy milk fermented by Bacillus subtilis SP-8-5 and Lactiplantibacillus plantarum 4_3 exhibits sedative-hypnotic ability in vivo - Zhen Liu; Zhao-Ying Zeng; Yu-Jin Li; Bin Zhou; Shi-Yi Sun; Xia Ou; Hua Qi; Chen-Jian Liu; Xiao-Ran Li (Food Research International, 2026)

Impact of waste biomass binders on the pelletizing, combustion, and engineering feasibility of sludge–coal slime co-pelletized fuel - Hao-Ran Chen; Yi-Wen Yuan; Zhi-Hao Liu; Chang-Ji Huang; Shi-YuS Ren; Hou-Feng Wang; Raymond Jianxiong Zeng (Environmental Research, 2026)

Regulation mechanism of N2O and CH4 emissions during the pig manure composting amended with Polygonum Multiflorum Thunb - Ya-jun Duan; Hong-sheng Wu; Jiang-yu Yang; Zheng-tong Zhou; Tao-ran Shi; Cheng Cheng; Zhen-wei Li; Chun-fa Wu; Ming-chun Di; Yu-dong He; Feng-yi Hu (World Journal of Microbiology and Biotechnology, 2026)

A chimeric PRRSV vaccine with dual Nsp2 deletions elicits cross-lineage protection against heterologous challenge - Zhuo-ran Miao; Bo Han; Ling-zhai Meng; Zhen-hui Ren; Yi-han Lu; Jing Li; Wen Sun; Shi-qin Zhang; Jia Wang; Jin-jin Ma; Jia-Lu Li; Yu-tong Zhu; et al. (The Veterinary Journal, 2026)

Transforming erosion-prone basin into carbon sink: the role of check dams in regulating carbon cycle in a semi-arid basin - Yi Zeng; Nufang Fang; Lishan Ran; Ying Yu; Zhengang Wang; Fengbao Zhang; Zhihua Shi (Water Research, 2026)

Emergence of a novel porcine reproductive and respiratory syndrome virus strain inducing biphasic temperature fluctuations in Tianjin, northern China - Jia Wang; Yi-Han Lu; Bo-Han; Hai-Tao Yang; Xin-lei Li; Wen Sun; Shi-Qin Zhang; Zhuo-Ran Miao; Xue-Jiao Cheng; Chun-Xue You; Ying-Feng Sun (Research in Veterinary Science, 2026)

Low doses of chlorothalonil cause testicular impairment in mammals through the antimicrobial-like mechanism - Han-Zhang Wang; Yi-Ming Xiong; Shi-Lin Song; Qian-Cheng Zhao; Xuan-Yue Chen; Jing-Ran Gao; Yuan-Yuan Li; Zhan-Fen Qin (Journal of Hazardous Materials, 2026)

Magnetic Fe3O4-Modified CeO2 Composite for Efficient Removal of Oxytetracycline Hydrochloride: Adsorption Behavior and Mechanistic Insights - Jiayi Long; Guanhua Meng; Ran Liu; Qiuyue Yi; Xu Shi (Water, Air, & Soil Pollution, 2026)

Enhanced removal of cytotoxicity from wastewater by silica gel-activated ferrate (VI) - Si-Yi Shi; Yao Lu; Yi-Ran Wan; Chang-Jie Yuan; Wei Hu; Min Liu; Ying Chen; Ye Du (Journal of Hazardous Materials, 2026)

Close-packed metal organic frameworks enabled high-energy solid-state lithium metal batteries - Yining Zhang; Hongsheng Shi; Yuyao Zhang; Xin Chen; Shuanghong Wang; Jinjiang Liang; Qiong Yuan; Tianyi Gao; Ran Wei; Haochen Zhang; Tao Li; Tianquan Lin; et al. (Chemical Engineering Journal, 2026)

Strategic sampling for training a semantic segmentation model in operational mapping: Case studies on cropland parcel extraction - Rui Lu; Ronghua Liao; Ran Meng; Yingchu Hu; Yi Zhao; Yan Guo; Yingfan Zhang; Zhou Shi; Su Ye (Remote Sensing of Environment, 2025)

Genome-Wide Identification and Expression Profiling of Oryza Sativa Sulfotransferase Genes Associated with Oxyfluorfen and Fluroxypyr-Meptyl Metabolism - Li Qing Zeng; Xiao Yu Zhong; Nian Hua Teng; Xu Zhen Shi; Yi Zhuo Wang; Xi Ran Cheng; Ying Yu Zeng; Zhao Jie Chen (Tropical Plant Biology, 2025)

Identification, Characterization, and Expression Profiling of Oryza Sativa Betaine Aldehyde Dehydrogenase Genes Exposed to Realistic Environmental Contamination of Oxyfluorfen - Yi Zhuo Wang; Jun Jin Lu; Xu Zhen Shi; Ya Nan Qu; Li Qing Zeng; Xiao Liang Liu; Xi Ran Cheng; Yan Hui Wang; Zhao Jie Chen (Tropical Plant Biology, 2025)

Quantitative Evaluation of Incomplete Stent Apposition in Intracranial Aneurysms Using Optical Coherence Tomography: a Porcine Model Study - Zhuangzhuang Wei; Ji Ma; Zhike Zhang; Shuailong Shi; Shuhai Long; Shaofeng Shui; Lei Yan; Yan Song; Yi Tang; Ye Wang; Jie Yang; Yuncai Ran; et al. (Translational Stroke Research, 2025)

A low-resistance reducer optimization method and manufacturing process based on Bézier curves and machine learning - Ao Tian; Ruoyin Jing; Junkai Ren; Yingying Wang; Yibu Gao; Yi Wang; Yan Tian; Lei Shi; Zhong Yu; Shengrui Yu; Ran Gao (Building and Environment, 2025)

A ratiometric fluorescent probe for sensitive detection of benzoyl peroxide and hypochlorite in food - Shun-Qiang Cui; Xin-Yi Liang; Zhi-Qiang Cai; Hou-Qun Yuan; Qiu-Yu Zhang; Yi-Fan Xia; A.K.I.M.A.N.A. Sandra; Ling-Yi Guo; Ran Wang; Shi-Yu Zhao; Yan-Xia Li; Guang-Ming Bao (Food Chemistry, 2025)

A selenium nanozyme: Light/mercury dual-enhanced oxidase mimicry for simultaneous ultra-sensitive detection and efficient removal of mercury ions, and superior photocatalytic bacterial disinfection - Yu Shi; Dong-hui Li; Chi Zhang; Zheng-ren Wang; Yi-ran Wang; Ru-kang Chen; Yen-ho Chu; Yu-gang Shi; Rammile Ettelaie; Qing Gu (Water Research, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Antimicrobial p -terphenyl derivatives from the deep-sea cold seep-derived fungus Aspergillus candidus - Yi-Yi Liu; Jing-Ya Shi; Qi-Ran Liang; Guang-Ying Chen; Hai-Xin Chen; Zhuang Han; Xu-Hua Nong (Natural Product Research, 2025)

A comprehensive omics resource and genetic tools for functional genomics research and genetic improvement of sorghum - Chengxuan Chen; Fengyong Ge; Huilong Du; Yuanchang Sun; Yi Sui; Sanyuan Tang; Zhengwei Shen; Xuefeng Li; Huili Zhang; Cuo Mei; Peng Xie; Chao Li; et al. (Molecular Plant, 2025)

Targeting ferroptosis for the treatment of female reproductive system disorders - Rui Ye; Yi-ming Mao; Yi-ran Fei; Yue Shang; Ting zhang; Zhe-zhong Zhang; Yong-lin Liu; Jun-yu Li; Shi-liang Chen; Yi-bo He (Journal of Molecular Medicine, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Research on the source of cinnabar excavated from Sanxingdui site in China based on sulphur and mercury isotope analyses - Qinxin Jiang; Guangyi Sun; Honglin Ran; Yu Lei; Chong Wang; Zhenbin Xie; Fei Tang; Jian Yu; Bisu Zhou; Min Shi; Wan Peng; Chenghui Li; et al. (Archaeological and Anthropological Sciences, 2025)

Gigantic gastropods from the Middle Triassic Qingyan biota of Guizhou - Xin Sun; Li Tian; Chuan-Yuan Liu; Xiao He; Dao-Liang Chu; Xue Miao; Shi-Yan Zhang; Yi-Ran Cao; Pei-Shan Li; Jin-Nan Tong; Hai-Jun Song (Palaeoworld, 2024)

Robust fatigue markers obtained from muscle synergy analysis - Chen Zhang; Zi-jian Zhou; Lu-yi Wang; Ling-hua Ran; Hui-min Hu; Xin Zhang; Hong-qi Xu; Ji-peng Shi (Experimental Brain Research, 2024)

Low frequency ultrasound enhanced the antioxidant activity and isoflavones accumulation of soybean sprouts by inducing oxidant stress - Zhangning Qiao; Yanling Shi; Juanjuan Yi; Jiaqing Zhu; Qiaozhen Kang; Lingbo Qu; Ran Yang; Jike Lu; Changcheng Zhao (Food Bioscience, 2024)

Three novel umami peptides from watermelon soybean paste and the revelation of the umami mechanism through molecular docking with T1R1/T1R3 - Yuexin Yao; Yanling Shi; Juanjuan Yi; Jiaqing Zhu; Qiaozhen Kang; Lingbo Qu; Ran Yang; Jike Lu; Changcheng Zhao (Food Bioscience, 2024)

Experimental optimization and mechanism analysis of extracting flavonoids with the supramolecular solvents-based methods - Zhi-lu Yu; Shi-yi Hou; Li-mei Lin; Yu-ran Chu; Ya-mei Li; Zhi-min Zhang; Jing Yan; Bo-hou Xia (Sustainable Chemistry and Pharmacy, 2024)

Curvularin derivatives from the marine mangrove derived fungus Penicillium sumatrense MA-325 - Yi-Ran Wang; Yu-Liang Dong; Xiao-Ming Li; Xiao-Shan Shi; Hong-Lei Li; Ling-Hong Meng; Rui Xu; Bin-Gui Wang (Phytochemistry, 2024)

π-π Stacking constructing efficient charge channels for perovskite photovoltaics - Chun-Hao Chen; Fan Hu; Kai-Li Wang; Jing Chen; Tian-Yu Teng; Yi-Ran Shi; Yu Xia; Zhen-Huang Su; Xing-Yu Gao; Ilhan Yavuz; Zhao-Kui Wang; Liang-Sheng Liao (Science Bulletin, 2024)

A long way to go: impacts of urbanization on migrants’ livelihoods and rural ecology in less industrialized regions - Zhi-qi Zhang; Ming-jing Li; Wen-jun Li; Yi-ran Wei; Yi-lu Shi (Journal of Mountain Science, 2023)

Degradation of Levofloxacin by a green zero-valent iron-loaded carbon composite activating peroxydisulfate system: Reactivity, products and mechanism - Shi-Ting Huang; Yong-Qian Lei; Peng-Ran Guo; Wen-Xuan Zhang; Jing-Yi Liang; Xie Chen; Jing-Wei Xu; Zeng-Hui Diao (Chemosphere, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Matthew effect photoimmunotheranostics enabled by proton-driven nanoconverter - Jingjing Wang; Wei Zhang; Dachong Gu; Chunmei Chen; Wei Tang; Yi Ouyang; Xiaohong Liu; Shi-Yu Lu; Wei Zhang; Xingcai Zhang; Yulong Han; Jie Hu; et al. (Chemical Engineering Journal, 2023)

Deep Sc-RNA sequencing decoding the molecular dynamic architecture of the human retina - Lulin Huang; Runze Li; Lin Ye; Shanshan Zhang; Huaping Tian; Mingyan Du; Chao Qu; Shujin Li; Jie Li; Mu Yang; Biao Wu; Ran Chen; et al. (Science China Life Sciences, 2023)

Repaired surface structural imperfection of tin Wide-Bandgap perovskite films for photovoltaic application - Tian-Yu Teng; Fan Hu; Yan-Hui Lou; Jun-Jie Cao; Chun-Hao Chen; Yi-Ran Shi; Kai-Li Wang; Jing Chen; Zhao-Kui Wang; Liang-Sheng Liao (Chemical Engineering Journal, 2023)

Whole-genome sequencing and comparative genomic analysis of a pathogenic Enterocytozoon hepatopenaei strain isolated from Litopenaeus vannamei - Libao Wang; Hui Li; Wenjun Shi; Yi Qiao; Pan Wang; Zhijun Yu; Ran Zhao; Runhao Hu; Hui Shen; Jie Cheng; Ge Jiang; Xintong Huang; et al. (Aquaculture International, 2023)

Sesquiterpenoids and monoterpenoids from the water decoction of Valeriana officinalis L - Shi-Wei Li; Bian-Xia Xue; Tian-Tian Yang; Ran Li; Mingjie Zhang; Miao Wang; Li-Hua Zhang; Peng Zhang; Yi Zhang; Tao Wang; Shao-Xia Wang; Hong-Hua Wu (Phytochemistry, 2023)

Effects of soil and water conservation measures on sediment delivery processes in a hilly and gully watershed - Yi Zeng; Xiangdong Meng; Bing Wang; Mengjie Li; Dan Chen; Lishan Ran; Nufang Fang; Lingshan Ni; Zhihua Shi (Journal of Hydrology, 2023)

Chitin oligosaccharides for the food industry: production and applications - Ran Zhang; Qiong Zhao; Zhenwei Yi; Kaihang Zhang; Jinqi Shi; Liangliang Zhu; Yijia Chen; Jiayang Jin; Liming Zhao (Systems Microbiology and Biomanufacturing, 2023)

Andrographolide ameliorates hepatic steatosis by suppressing FATP2-mediated fatty acid uptake in mice with nonalcoholic fatty liver disease - Li-Sha Ran; Ya-Zeng Wu; Yi-Wen Gan; Hong-Lian Wang; Li-Juan Wu; Chun-Mei Zheng; Yao Ming; Ran Xiong; Yong-Lin Li; Shi-Hang Lei; Xue Wang; Xiao-Qing Lao; et al. (Journal of Natural Medicines, 2023)
Excessive intrahepatocellular lipid accumulation or steatosis is caused by abnormal lipid metabolism and a common character of nonalcoholic fatty liver disease (NAFLD), which may progress into cirrhosis and hepatocellular cancer. Andrographolide (Andro) is the primary active ingredient extracted from Andrographis paniculata , showing a protective role against dietary steatosis with the mechanism not fully understood. In this study, we showed that administration of Andro (50, 100, and 200 mg/kg/day for 8 weeks, respectively) attenuated obesity and metabolic syndrome in high-fat diet (HFD)-fed mice with improved glucose tolerance, insulin sensitivity, and reduced hyperinsulinemia, hyperglycemia, and hyperlipidemia. HFD-fed mice presented hepatic steatosis, which was significantly prevented by Andro. In vitro, Andro decreased the intracellular lipid droplets in oleic acid-treated LO2 cells. The selected RT-PCR array revealed a robust expression suppression of the fatty acid transport proteins (FATPs) by Andro treatment. Most importantly, we found that Andro consistently reduced the expression of FATP2 in both the oleic acid-treated LO2 cells and liver tissues of HFD-fed mice. Overexpression of FATP2 abolished the lipid-lowering effect of Andro in oleic acid-treated LO2 cells. Andro treatment also reduced the fatty acid uptake in oleic acid-treated LO2 cells, which was blunted by FATP2 overexpression. Collectively, our findings reveal a novel mechanism underlying the anti-steatosis effect of Andro by suppressing FATP2-mediated fatty acid uptake, suggesting the potential therapeutic application of Andro in the treatment of NAFLD. Graphical abstract

Categorizing objects from MEG signals using EEGNet - Ran Shi; Yanyu Zhao; Zhiyuan Cao; Chunyu Liu; Yi Kang; Jiacai Zhang (Cognitive Neurodynamics, 2022)

A new indole alkaloid with HUVEC proliferation activities from Nauclea officinalis - Shi-Ying Mai; Yong-Hui Li; Xu-Guang Zhang; Yi-Ran Wang; Jun-Qing Zhang; An Jia (Natural Product Research, 2021)

Anaerophilus nitritogenes gen. nov., sp. nov., isolated from salt lake sediment in Xinjiang Province, China - Ran Zhang; Yan Zeng; Tian-Qi Wang; Xin-Mei Wang; Yi-Yu Shi; Jia-Tian Zou; Cong Sun; Gui-Shan Zhang; Wei-Yan Zhang; Min Wu (Antonie van Leeuwenhoek, 2020)

Complete genome sequence and comparative genome analysis of a new special Yersinia enterocolitica - Guoxiang Shi; Mingming Su; Junrong Liang; Ran Duan; Wenpeng Gu; Yuchun Xiao; Zhewen Zhang; Haiyan Qiu; Zheng Zhang; Yi Li; Xiaohe Zhang; Yunchao Ling; et al. (Archives of Microbiology, 2016)

Evolution of the microbial community of the biofilm in a methane-based membrane biofilm reactor reducing multiple electron acceptors - Ran Chen; Yi-Hao Luo; Jia-Xian Chen; Yin Zhang; Li-Lian Wen; Ling-Dong Shi; Youneng Tang; Bruce E. Rittmann; Ping Zheng; He-Ping Zhao (Environmental Science and Pollution Research, 2016)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Abundance and composition of ammonia-oxidizing bacteria and archaea in different types of soil in the Yangtze River estuary - Xiao-ran Li; Yi-ping Xiao; Wen-wei Ren; Zeng-fu Liu; Jin-huan Shi; Zhe-xue Quan (Journal of Zhejiang University-SCIENCE B, 2012)